Integrating Corporate Strategy with Digital Transformation, Cybersecurity, and Sustainability - Arief Bowo Prayoga Kasmo; Surender Mor; Lucky Nugroho; Mohamad Rohadi; Adhy Purnama (Jurnal Lemhannas RI, 2025)
Purpose: This study proposes an integrative strategic model that aligns corporate vision, mission, and long-term goals with digital transformation, cybersecurity, and sustainability in response to disruption and geopolitical complexity in the Indo-Pacific region. Study Design/Methodology/Approach: Using a descriptive qualitative method, the study draws on Absorptive Capacity Theory and Actor-Network Theory. Secondary data are analysed through literature and document review to assess how organisations absorb external knowledge and coordinate across sectors to develop resilient strategies. Findings: The study identifies a strategic gap between corporate objectives and the implementation of digital and sustainability initiatives. It highlights the urgency of embedding ESG principles, digital security, and adaptive planning into strategic frameworks. The proposed model promotes a learning-oriented and networked organisation capable of aligning operational resilience with long-term goals. Originality/Value: This study introduces a novel interdisciplinary framework that integrates strategic management, ESG transformation, and cybersecurity. Unlike conventional models, it places equal emphasis on innovation, risk governance, and sustainability. The model offers practical insights for corporate leaders and informs policymakers in designing integrated digital governance and ESG metrics to strengthen national resilience.